Dietary Intake and Chronic Disease Prevention - Noce, Annalisa; Romani, Annalisa; Bernini, Roberta (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint describes how lifestyle changes can impact the incidence and progression of chronic non-communicable diseases. In this context, regular physical activity and heathy nutritional habits are very important. Moreover, natural bioactive compounds could represent a new adjuvant therapy in the clinical management of these pathological conditions.